Nigeria - Competitiveness and Growth : Country Economic Memorandum, Volume 2. Main Report - World Bank (Washington, DC, 2012)
The theme of this report is Nigeria's competitiveness and growth. This report consequently focuses on constraints, opportunities and strategic choices associated with increasing productivity and growth of the Nigerian economy on a sustained basis. Its objective is not to present a "blueprint" for Nigeria's growth but rather to raise issues and provide some options for the consideration of policy makers and other Nigerian stakeholders. The report is structured in four main sections. The first section analyzes Nigeria's growth history, examines the recent growth pick up and assesses its sustainability. The second section analyses how the critical constraints to competitiveness and growth may be addressed. The third section discusses how trade -domestic and external - can be used more effectively to drive growth and poverty reduction. The final chapter provides policy conclusions and suggestions on what could be key elements of a growth agenda for Nigeria. The analysis in this report suggests the following key elements for a growth strategy for Nigeria: 1) Strengthening actions to tackle the most immediate constraints to the competitiveness of the economy presented by infrastructure and the business environment; 2) Using domestic trade more effectively to enhance productivity and competitiveness by strengthening their functioning, and building stronger linkages between the oil and non-oil sectors, and over time strengthening Nigeria's integration into global markets; 3) Ensuring that the poor can participate more fully in growth by placing urgent emphasis on (i) finding ways to give back some of the proceeds of oil windfall directly to Nigerians; (ii) raising agricultural productivity-including through enhanced technology; and (iii) encouraging the transition from informality to the formal sector; and 4) Building the human capital and technological base of the economy over the longer term.